Yoga at Every Size: A Preliminary Evaluation of a Brief Online Size-Inclusive Yoga and Body Gratitude Journaling Intervention to Enhance Positive Embodiment in Higher Weight College Women - Webb, Jennifer B.; Padro, Meagan P.; Thomas, Erin Vinoski; Davies, Alexandria E.; Etzel, Lena; Rogers, Courtney B.; Heredia, Natalia I. (Frontiers in Global Women's Health, 2022)
The present pilot randomized controlled trial (RCT) evaluated the feasibility, acceptability, and preliminary efficacy of a 4-week online yoga and body gratitude journaling intervention for strengthening positive embodiment among racially-diverse higher weight college women. Seventy-five participants were initially randomized to either the yoga condition (n = 36) or to a wait-list control (n = 39). Participants completed measures of positive and negative body image, weight bias internalization, self-compassion, drive for leanness, and physical activity acceptance at both baseline and post. Preliminary results among the 42 analyzed completers (mean age = 20.9, SD = 2.4; 30% Black or African American) revealed acceptable feasibility given the low-intensity nature of the intervention reflected in a 36% attrition rate. Self-reported adherence was strong for the yoga component with 81% of participants indicating that they practiced with the videos > 3-4 times per week as suggested. Although 71% reported completing the body gratitude journal > 1-2 times per week, daily adherence was minimal. Acceptability was also high among participants randomized to the yoga condition as indicated by 86% expressing at least moderate levels of satisfaction with the overall program. Qualitative feedback from participants further supported the acceptability of the program and pointed to important areas in further refining the protocol in the future. Preliminary efficacy was supported by significant reductions in internal body shame and gains in body appreciation, functional body appreciation, functional body satisfaction, functional body awareness, and behavioral commitment to physical activity engagement among the yoga versus wait-list control participants. These promising findings once replicated in larger, higher-powered trials may have important implications for extending the reach and accessibility of mind-body wellness practices like yoga to benefit racially-/ethnically-diverse college women of higher weight. This research is further responsive to the growing need for efficacious remotely-delivered, and scalable behavioral health interventions in the ongoing era of the COVID-19 pandemic. However, additional research is warranted to explore ways of enhancing engagement of participants with lower levels of positive embodiment and to further incentivize the journaling component of the intervention.